Researcb on Application Bidirectional Identity Autbentication Scbeme Based on Mobile Pbone Token - Zhaohua Zheng; Jinlian Peng; Jieren Cheng (Dianxin kexue)
With the development of mobile information, security problems of mobile applications had become the focus of attention of the user. Authentication has many solutions. The dynamic password authentication technology is currently the most effective solution. After analyzing the current dynamic password shortcomings, a dynamic password authentication scheme based on improved mobile phone token to challenge ／ response was proposed. It uses fingerprint as the evidence of token, and can be two-way authentication, and has segment of double channel encryption communication. In addition, the security was analyzed. Analysis results show that the scheme is convenient to use and has high security and low cost. The scheme fully meets the higher security level of identity authentication on application requirements in mobile communication.